Effect of epinephrine and dibutyryl cyclic AMP on Δ5-desaturation activity of rat liver microsomes - Tacconi de Gómez Dumm, Irma Nelva (1980)
The effect of epinephrine and dibutyryl cyclic AMP on the oxidative desaturation of [1-14C]-eicosatrienoic acid to arachidonic acid of rat liver microsomes has been studied. Epinephrine, at a dose of 1 mg/kg/body weight, produced a significant decrease on Δ5-desaturation activity 3 hr after the injection. This effect was maintained up to 12 hr and reached the control values 48 hr after the hormone administration. Dibutyryl cyclic AMP treatment for 24 hr (5 mg/8 hr/100 g body weight) also produced a significant decrease of the conversion of eicosatrienoic acid to arachidonic acid in rat liver microsomes. The effect of epinephrine on Δ5-desaturation activity was postulated to be evoked through an increase of the intracellular concentration of cyclic AMP.